An audit on the clinical and laboratory profile of patients with different variants of Guillain-Barre syndrome and effect of various treatment strategies on their recovery - Abhijit Prithviraj Chavan; Suhrud Jayadev Panchawagh; Abhijit Ramratan Pundkar; Ingole, Jitendra R. (International Journal of Research in Medical Sciences, 2023)
Background: Guillain-Barre syndrome (GBS) is an immune-mediated disorder of the peripheral nervous system, causing muscle weakness, paralysis, and sensory deficits. Its treatment mainly involves supportive care, immunomodulatory therapies such as intravenous immunoglobulin (IVIg) and plasma exchange (PE), and rehabilitation. Several randomized controlled trials (RCTs) and meta-analyses have evaluated the efficacy and safety of apheresis in GBS, but the results have been conflicting and limited by methodological issues. Methods: This is a retrospective study with a sample of 30 patients carried out at neurology OPD of tertiary care centre in Pune, Maharashtra over a period of 32 months from July 2020 and February 2023. Patients were followed up for six months, and their outcomes were compared in terms of the improvement of clinical disability scores, the need for mechanical ventilation, and the time to recovery of walking ability and other functional outcomes. Results: Apheresis treatment significantly improved the clinical disability scores and NCV recovery of patients with GBS in comparison to IVIg and corticosteroids. Moreover, patients who received apheresis treatment showed a shorter time to recovery of walking ability and other functional outcomes than those who did not. Symptomatic differences were seen between patients with different subtypes of GBS, but there was no difference in the response to apheresis or IVIg between subtypes. Conclusions: Treatment with apheresis should be considered in patients not responding to conservative management. Earlier treatment with apheresis has shown to have good clinical and electrophysiological outcomes regardless of the GBS subtype.